Chronic Treatment with Fluoxetine Induces Sex-Dependent Analgesic Effects and Modulates HDAC2 and mGlu2 Expression in Female Mice - Zammataro, Magda; Merlo, Sara; Barresi, Massimo; Parenti, Carmela; Hu, Huijuan; Sortino, Maria A.; Chiechio, Santina (Frontiers in Pharmacology, 2017)
Gender and sex differences in pain recognition and drug responses have been reported in clinical trials and experimental models of pain. Among antidepressants, contradictory results have been observed in patients treated with selective serotonin reuptake inhibitors (SSRIs). This study evaluated sex differences in response to the SSRI fluoxetine after chronic administration in the mouse formalin test. Adult male and female CD1 mice were intraperitoneally injected with fluoxetine (10 mg/kg) for 21 days and subjected to pain assessment. Fluoxetine treatment reduced the second phase of the formalin test only in female mice without producing behavioral changes in males. We also observed that fluoxetine was able to specifically increase the expression of metabotropic glutamate receptor type-2 (mGlu2) in females. Also a reduced expression of the epigenetic modifying enzyme, histone deacetylase 2 (HDAC2), in dorsal root ganglia (DRG) and dorsal horn (DH) together with an increase histone 3 acetylation (H3) level was observed in females but not in males. With this study we provide evidence that fluoxetine induces sex specific changes in HDAC2 and mGlu2 expression in the DH of the spinal cord and in DRGs and suggests a molecular explanation for the analgesic effects in female mice.